A RELEVANCE-THEORETIC ANALYSIS OF YEAH AS A DISCOURSE MARKER - Thuy, Dam Ha (VNU Journal of Foreign Studies; Vol 35 No 3DO - 10.25073/2525-2445/vnufs.4377, 2019)
The paper attempts to explain English native speakers’ use of the discourse marker yeah from a relevance-theoretic perspective (Sperber & Wilson, 1995). As a discourse marker, yeah normally functions as a continuer, an agreement marker, a turn-taking marker, or a disfluency marker. However, according to Relevance Theory, yeah can also be considered a procedural expression, and therefore, is expected to help yield necessary constraints on the contexts, which facilitates understanding in human communication by encoding one of the three contextual effects (contextual implication, strengthening, or contradiction) or reorienting the audience to certain assumptions which lead to the intended interpretation. Analyses of examples taken from conversations with a native speaker of English suggest that each use of yeah as a discourse marker is able to put a certain type of constraints on the relevance of the accompanying utterance. These initial analyses serve as a foundation for further research to confirm its multi-functionality as a procedural expression when examined within the framework of Relevance Theory.